Post‐chemotherapy retroperitoneal teratoma in nonseminomatous germ cell tumors: Do predictive factors exist? Results from a national multicenter study. Issue 8 (18th November 2016) - Dusaud, Marie; Malavaud, Bernard; Bayoud, Younes; Sebe, Philippe; Hoepffner, Jean Luc; Salomon, Laurent; Houlgatte, Alain; Pignot, Géraldine; Rigaud, Jérome; Fléchon, Aude; Pfister, Christian; Rouprêt, Morgan; et al.
Abstract : Background and Objectives: To identify predictive preoperative factors of the presence of teratoma in retroperitoneal lymph node dissection specimens. Methods: We performed a 20 years multicenter retrospective analysis of all patients who underwent retroperitoneal lymph node dissection for residual masses after chemotherapy (PC‐RPLND). Patients had undergone PC‐RPLND after chemotherapy for advanced testicular cancer. The histologic components of the primary tumor were compared with those of the residual masses using logistic regression. Results: A total of 469 NSGCT patients underwent PC‐RPLND (complete data available for 211). By PC‐RPLND, necrosis was found in 84 cases, teratoma in 102 cases, and viable tumor in 25 cases. The univariate and multivariate analyses showed that teratoma ( P  = 0.001 and P  = 0.002, respectively) and yolk sac tumor ( P  = 0.009 and P  = 0.035, respectively) in orchiectomy specimens were statistically significant predictors of the presence of teratoma in retroperitoneal lymph nodes. Conclusions: PC‐RPLND is the standard treatment for any supracentimetric residual lesion. This procedure is associated with a high morbidity, and almost half patients are overtreated. The presence of teratoma and yolk sac tumor in the orchiectomy specimen were independent significant predictors of teratoma in retroperitoneal masses. J. Surg. Oncol. 2016;114:992–996 . © 2016 Wiley Periodicals, Inc.